Enhancing organizational resilience through employee job engagement: The role of creative self-efficacy and flexible human resource practices - Muhammad Zakki Al Achtaar (Journal of Management and Business Insight, 2025)
Purpose-This study investigates the effects of employee creative self-efficacy and flexible human resource practices on organizational resilience, with employee job engagement as a mediating variable. While previous studies on organizational resilience have mainly focused on structural and policy-based factors, this research extends the literature by emphasizing the role of individual psychological resources in building resilience within organizations. Methodology-This study employed a quantitative survey design involving 131 employees of logistics companies in the Yogyakarta, Indonesia, selected through purposive sampling. Data were analyzed using partial least squares–structural equation modeling to examine direct and indirect relationships among employee creative self-efficacy, flexible human resource practices, employee job engagement, and organizational resilience. Findings-The results demonstrate that employee creative self-efficacy has a positive and significant effect on both employee job engagement and organizational resilience. Employee job engagement also significantly enhances organizational resilience and serves as a mediating mechanism between creative self-efficacy and resilience. In contrast, flexible human resource practices show no significant direct or indirect effect on organizational resilience, indicating that formal human resource flexibility alone is insufficient to foster resilience without active employee engagement. Research Limitations-This study is limited by its cross-sectional design and reliance on self-reported measures, which may introduce common method bias. Additionally, the focus on a single industry and regional context may constrain the generalizability of the findings. Novelty-This study contributes novel insights by demonstrating that organizational resilience is driven more strongly by individual psychological resources than by formal human resource flexibility. It further identifies employee job engagement as the critical mechanism that transforms creative self-efficacy into organizational adaptive capacity. By revealing the limited role of flexible human resource practices in the absence of employee engagement, this research challenges prevailing structural-centric resilience models and offers a micro-foundational perspective on resilience in high-pressure service environments.